High-quality processing method for repairing plain weaving type CFRP damaged area

By using the two steps of focusing and polarizing laser scanning in the CFRP damage area, combined with milling processing and ultraviolet laser treatment, the problem of low repair efficiency of the CFRP damage zone in the existing technology has been solved. Repair effect.

CN119369769AActive Publication Date: 2025-01-28SOUTHWEST JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411503380.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the prior art, the bonding method for repairing CFRP damage zones is inefficient and lacks repeatability. Milling processing will cause fiber breakage, fiber fragmentation and resin coating, affecting the bonding strength.

Method used

采用两步法,首先在焦距条件下多次扫描CFRP工件,形成接近层去除的阶梯状结构,然后在偏焦条件下使用紫外激光清理表面树脂和纤维碎片,铣削加工补片并进行紫外激光处理,最终进行胶接修复。

Benefits of technology

The high -quality formation of the flat -striped woven CFRP damage area is achieved, the surface resin and fiber fragments are removed, the fresh carbon fiber tube is exposed, and the repair performance and strength of the subsequent glue connection is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369769A_ABST
    Figure CN119369769A_ABST
Patent Text Reader

Abstract

The invention discloses a high-quality processing method for repairing a plain weaving type CFRP damaged area, which comprises the following steps: S1, ablating the plain weaving type CFRP by ultraviolet laser to obtain the relationship between the scanning times and the ablating depth; and S2, milling is conducted according to the ultraviolet laser ablation performance, a two-step machining method of ultraviolet laser aftertreatment is provided, and surface resin cleaning within the milling depth range of 200-500 micrometers is achieved. The two-step method provided by the invention can meet the high-quality processing of the plain weaving type CFRP damaged area repair. Resin, fiber fragments, resin remains and the like on the surface of the milled CFRP material are removed through an ultraviolet laser offset-focus processing treatment method, a large number of fresh carbon fiber tubes are exposed on the surface after cleaning, and the repairing performance can be improved during follow-up glue joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of processing composite materials CFRP, and in particular relates to a high-quality processing method for repairing a damaged area of ​​a plain-weave CFRP. Background Art

[0002] CFRP is widely used in aerospace, high-speed rail, automobile and other fields due to its advantages such as light weight, high strength, corrosion resistance and design flexibility. During the manufacturing process, the material is affected by temperature gradients or uneven pressure during solidification, resulting in defects such as internal holes and delamination. During service, CFRP is susceptible to damage such as scratches, cracks, and impacts due to harsh environments. However, these damages will weaken the mechanical properties of the material. Replacing structural parts in the damaged area is costly, so efficient and high-performance damaged area repair of composite materials is an important research task.

[0003] There are two main methods for composite material repair at present, namely mechanical connection repair and adhesive repair. Compared with mechanical connection, adhesive repair has the advantages of reducing stress concentration, small weight gain, and good fatigue resistance. Therefore, current scholars have conducted a lot of research on adhesive repair of composite materials. In this process, it is necessary to first excavate the damaged area, process a stepped structure to improve the interlocking effect with the subsequent patch, and expose the carbon fiber to prepare for reconstruction. The traditional manual polishing method is inefficient and lacks repeatability.

[0004] At present, the literature on CFRP damage repair focuses on laminates, and there are few studies on plain woven CFRP structural parts. Therefore, it is urgent to carry out research on the repair of damaged areas of plain woven CFRP structural parts and reveal the surface forming mechanism of the material.

[0005] In order to repair the damaged area of ​​plain woven CFRP structural parts, the patch needs to be glued to the excavated area. In order to ensure that the patch can fit the excavated area highly to restore the aerodynamic performance of the material, the material needs to be precisely formed. Milling, as a deterministic processing method, can meet the precision requirements. However, after milling, a large amount of resin will inevitably appear on the surface, and there will be different degrees of fiber fragments, fiber-matrix separation and other damage, which will affect the subsequent bonding performance. Previous studies have shown that the use of ultraviolet laser defocusing processing can remove a large amount of resin on the surface without destroying the surface fiber integrity. Summary of the invention

[0006] The purpose of the present invention is to provide a high-quality processing method for repairing a damaged area of ​​a plain woven CFRP, so as to solve the problem that the manual grinding method of the prior art repair by bonding is inefficient and lacks repeatability; and the milling of CFRP composite materials will inevitably cause fiber breakage, fiber fragments, resin smearing, fiber-matrix separation, etc., which will affect the bonding strength of subsequent repairs.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A high-quality processing method for repairing a plain woven CFRP damaged area comprises the following steps:

[0009] Step S1, firstly scanning a plain woven CFRP workpiece multiple times under a focal length condition to obtain a stepped workpiece with a close layer removed;

[0010] Step S2, scanning the surface of the ablated CFRP workpiece under a defocus condition to clean the surface resin of the CFRP workpiece;

[0011] Step S3, for the pit obtained after laser ablation, the workpiece is milled to obtain a patch matching the pit, and the surface resin and fiber fragments of the patch after milling are cleaned with ultraviolet laser;

[0012] Step S4, bonding the processed patch to the CFRP workpiece to complete the repair of the CFRP workpiece.

[0013] According to the above technical solution, in step S1, the scanning speed of scanning the plain woven CFRP workpiece is 115 mm / s-1840 mm / s, and the filling spacing ranges from 5 μm to 28 μm.

[0014] According to the above technical solution, in step S2, the speed range of scanning the surface of the CFRP workpiece under the defocus condition is 125mm / s-750mm / s, and the filling spacing range is 5μm-30μm.

[0015] According to the above technical solution, in step S2, the scanning speed parameter is adjusted according to the following formula:

[0016]

[0017] Where v is the scanning speed, f is the frequency, and d is the spot diameter.

[0018] According to the above technical solution, in step S2, the filling spacing parameter is adjusted according to the following formula:

[0019]

[0020] Where p is the fill spacing and d is the spot diameter.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The two-step method proposed in the present invention can meet the high-quality forming of plain woven CFRP damaged area repair. The content of protection is that the surface resin, fiber fragments and resin debris of the milled CFRP material are removed by ultraviolet laser defocusing processing method. After cleaning, a large number of fresh carbon fiber tubes are exposed on the surface, which can improve the repair performance during subsequent bonding. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram showing the relationship between the ablation depth and the number of scans of the present invention;

[0024] Figure 2 A schematic diagram for verifying the method of the present invention;

[0025] Figure 3 It is a schematic diagram of two independent surface treatment operations in the focal length and defocused state of the present invention;

[0026] Figure 4 This is a schematic diagram of the laser experiment of the present invention;

[0027] Figure 5 This is a comparative schematic diagram of the laser experiment of the present invention;

[0028] Figure 6 It is a schematic diagram of the macroscopic multi-layer three-dimensional morphology before and after laser treatment of the present invention;

[0029] Figure 7 It is a schematic diagram of the surface line profile after milling of the present invention;

[0030] Figure 8 It is a schematic diagram of the surface line profile after laser processing of the present invention;

[0031] Fig. 9 An optical microscope image of the ablated surface after laser processing of the present invention;

[0032] Fig.10 This is a schematic diagram of the positive-biased laser ablation experiment of the present invention;

[0033] Fig.11 is a schematic diagram of the target sample;

[0034] Fig.12 It is a schematic diagram of the processing flow of the present invention;

[0035] Fig.13 A scanning electron microscope image of the features of the present invention;

[0036] Fig.14The surface morphology in the upper meridian direction with different milling parameters of the present invention;

[0037] Fig.15 This is the SEM image of the same position after laser treatment in the present invention;

[0038] Fig.16 This is a schematic diagram of the three-dimensional stepped geometry after laser processing according to the present invention;

[0039] Fig.17 It is a schematic structural diagram of the surface view and the side view of the material of the present invention;

[0040] Fig.18 This is a schematic diagram of the laser scanning process of the present invention;

[0041] Fig.19 This is a schematic diagram of cleaning residual resin on the surface after molding by the off-focus laser processing of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Embodiment 1

[0044] A high-quality processing method for repairing a plain woven CFRP damaged area comprises the following steps:

[0045] Step S1, firstly scanning a plain woven CFRP workpiece multiple times under a focal length condition to obtain a stepped workpiece with a close layer removed;

[0046] Step S2, scanning the surface of the ablated CFRP workpiece under a defocus condition (i.e., the condition that the laser is focused to a focal point through a galvanometer) to clean the surface resin of the CFRP workpiece;

[0047] Step S201, first scan the workpiece multiple times under the focal length condition to obtain a stepped workpiece with the near layer removed; since the plain woven CFRP is woven from yarns, the yarns are fiber bundles composed of a large number of carbon fiber tubes, the surface and side views of this material are as follows Fig.17 As shown, from top to bottom, it is composed of yarns in two orthogonal directions. Approaching layer removal is approaching the removal of a layer of yarn, such as Fig.11 shown.

[0048] Step S202, then use the off-focus laser processing method to clean the residual resin on the surface after molding (such as Fig.13shown).

[0049] In step S201, the scanning method is specifically as follows: fill a 8mm*8mm square area of ​​the workpiece with a scanning angle of 45°, such as Fig.19 As shown in the figure, a scan is performed when a square area is completely filled, and the progressive angle is increased by θ = 90° each time to ensure uniform ablation energy.

[0050] According to the ablation characteristics of different scanning speeds and filling spacing under focal length conditions obtained in step S1, they are divided according to the morphology: severe ablation, partial ablation and incomplete ablation. On this basis, according to the characteristics of strong laser energy density under focal length conditions, multiple repeated scans are performed under these conditions to obtain depth-controlled laser ablation performance. Multiple scans under severe ablation processing conditions will cause pits on the surface and fiber passivation, which will seriously damage the material matrix and is not conducive to achieving depth-controlled laser ablation. Under partial ablation conditions, as the number of scans increases, the width of the fiber clusters with undulations on the surface gradually decreases, and the next layer of resin and fiber is gradually exposed. When the number of scans reaches 16 times, a layer of yarn (approaching the layer) is almost completely removed, and new braided yarns are exposed. This phenomenon was almost reproduced when scanning 32 times, which shows that scanning 16 times under this condition can nearly remove a layer of braided yarn.

[0051] In addition, under the condition of incomplete ablation, a similar process was almost reproduced because the laser energy density was low, and this process required 24 scans to achieve.

[0052] According to the ablation results obtained by multiple laser scans under the above focal length conditions, a stepped three-dimensional structure was constructed. The processing parameters v = 805mm / s, the filling spacing d = 14μm, each layer was scanned 16 times, three layers were processed, and a total of 48 scans were performed. The processing flow diagram is shown in the figure. Fig.12 As shown, the ablation area is a square of 8mm*8mm, and the circles in the middle are 2mm, 4mm, and 6mm from top to bottom.

[0053] For the pits obtained after laser ablation, the workpiece was milled to obtain a patch that matched it, and the surface resin and fiber fragments of the patch after milling were cleaned with ultraviolet laser; and the surface scanning electron microscope images after milling and before and after ultraviolet laser treatment, EDS element analysis results and the surface profile data of the final three-dimensional patch were compared. The multiple scans of the above ultraviolet laser ablation cannot achieve precise removal, so milling, a deterministic processing method, is used to achieve precise forming of the patch surface, thereby ensuring the repair performance after the patch is bonded to the damaged area.

[0054] Step S4, bonding the processed patch to the CFRP workpiece to complete the repair of the CFRP workpiece.

[0055] The two-step method proposed in the present invention can meet the requirements of high-precision and high-quality surface forming of plain woven CFRP damaged area patches. The CFRP material after milling is processed by ultraviolet laser defocusing to remove surface resin, fiber fragments and resin debris, etc. After cleaning, a large number of fresh carbon fiber tubes are exposed on the surface, which can improve the repair strength during subsequent bonding.

[0056] Embodiment 2

[0057] This embodiment is a further refinement of the first embodiment.

[0058] In step S1, it is necessary to study the mechanism of action of UV laser ablation of plain woven CFRP, specifically: characterize the morphology after a single scanning process by adjusting the scanning speed, filling spacing and defocus, and the specific experimental parameters are shown in Table 1. Finally, a clean surface with no surface resin residue and good fiber integrity is obtained. Since a pulsed laser is used, the overlap of the light spots will cause heat accumulation. The present invention plans the scanning speed and filling spacing parameters according to the overlap calculation formula. The overlap calculation formula along the scanning direction is as follows:

[0059]

[0060] Where v is the scanning speed, f is the frequency, and d is the spot diameter.

[0061] In addition, the calculation formula for the overlap in the filling spacing direction is as follows:

[0062]

[0063] Where p is the fill pitch and d is the spot diameter.

[0064] Based on the first step, multiple scans are performed under the focus condition to obtain the relationship between the number of scans and the ablation depth.

[0065] Table 1 UV laser scanning parameters

[0066]

[0067] Based on the above UV laser ablation performance and multiple scanning results, a hybrid processing method is proposed to combine efficient layer-by-layer removal and high-quality ablated surface, and the reliability and repeatability of UV defocus processing are verified in three-dimensional structures. First, multiple scanning is performed under focal length conditions to achieve a stepped three-dimensional structure with close layer removal (schematic diagram as shown in the figure). Fig.11 Then, the residual resin on the surface after molding is cleaned by using the off-focus laser processing method.

[0068] The relationship between ablation depth and scan number is shown in the following table.

[0069] Table 2 Relationship between ablation depth and scanning times

[0070]

[0071] In order to explore the performance of UV laser repair under different milling parameters, the present invention designed a total of 7 groups of experiments based on the full factor variables. These full factors are milling depth, feed per tooth and cutting speed. The specific parameters are shown in Table 3. Each group of experiments was performed twice, and the second experiment was repaired with UV laser. The schematic diagram of the two-step experimental method is shown in Figure 2 As shown in (a), (b).

[0072] Table 3 Milling experiment parameter planning

[0073]

[0074] Previous work has proven that UV laser can remove residual resin on the surface in a defocused state without damaging the integrity of the fiber. Therefore, the present invention continues the special surface treatment parameters used previously to remove the surface resin after milling to expose the carbon fiber in preparation for subsequent bonding. The specific parameters are shown in Table 4 below, with the frequency and pulse width being 50kHz and 14ns respectively.

[0075] Table 4 Laser experiment parameter planning

[0076]

[0077] Removing the surface resin and exposing a large amount of carbon fiber is beneficial to improving the subsequent repair strength. Therefore, the present invention compares the surface morphology of plain woven CFRP before and after laser repair. First, a metallographic microscope (Axio Lab.A1, ZEISS) was used to observe the brightness changes of the fiber clusters. Further, a scanning electron microscope (JSM-IT500, JEOL) with an energy spectrometer (Ultim Max, OXFORD INSTRUMENTS) was used to characterize the micromorphology, and the elemental composition of the processed surface was analyzed. Since epoxy resin is not conductive, the material was sputtered with a gold spraying instrument (EMACE200, LEICA) before shooting the scanning electron microscope, with a thickness of 15nm. In the final formation of the three-dimensional stepped structure, a 3D profiler (VR-6200, KENENCE) was used to measure the removal depth and obtain the surface profile.

[0078] Previous studies have proposed a hybrid laser processing strategy to balance efficient step ablation and excellent surface quality, in which two independent surface treatment operations including on-focus and off-focus states are performed consecutively (e.g. Figure 3The former is to generate the surface with laser quickly and with high precision, while the latter is to remove the residual resin and attached particles on the processed surface. In order to prove its feasibility, the laser experiment was divided into two steps, as shown in Figure 4 shown. Figure 5 The surface morphology of the same parameters but without the second step of defocusing treatment is compared Figure 4 a3, b3 and Figure 5 c, d, it can be seen that the second step of laser cleaning and activation is necessary.

[0079] The present invention proves the reliability of the two-step method by comparing the surface morphology, EDS spectrum results and three-dimensional structure contour before and after laser treatment, providing guidance for the high-precision and high-quality manufacturing of plain woven CFRP damaged area patches.

[0080] The same milling cutter was used to continuously process two three-dimensional stepped structures, and the results of the second experiment were specially processed by ultraviolet laser to obtain the macroscopic multi-step three-dimensional morphology before and after laser treatment, such as Figure 6 (a) is the surface morphology without treatment, (b) is the surface morphology after laser treatment, the structural schematic diagram and flow chart are shown in Figure 2 (c) as shown.

[0081] Furthermore, the surface profile of the three-dimensional structure was obtained using a 3D profilometer to analyze whether laser repair has a significant effect on the profile accuracy of the stepped surface. Figure 7 and Figure 8The surface line profiles after milling and laser treatment are shown respectively. (a) is the profile of section AA, and (b) is the profile of section BB. The actual three-dimensional structure is 15mm×15mm in length and width. To avoid the error caused by the boundary, the length of the extracted line profile is 14mm. Obviously, the profile of the original rough surface is not flat, and the height difference between the upper and lower parts even reaches 67μm, which is determined by the undulating yarns of the plain woven CFRP material structure itself. In contrast, the surface after milling is relatively flat, and the height difference between the upper and lower parts is within 22μm. In addition, the surface height difference after UV laser scanning has not changed significantly, and the height difference is within 21μm, which shows that laser treatment does not affect the removal depth accuracy of the material. The three-dimensional profile is based on the bottom layer as the reference. Therefore, by calculating the height difference between each layer and the bottom layer, the surface ablation depth results before and after laser treatment are quantitatively analyzed and shown in Table 4. The results show that laser treatment does not affect the removal depth of the material because the UV laser only removes the surface resin and debris. It should be pointed out that during the first milling of the three-dimensional stepped structure, due to the undulating structure of the yarn of the material itself, errors may occur during the tool setting process, so the height difference between the third layer and the initial surface is slightly greater than 500μm, and the rest of the results are not affected. Compared with laser ablation to remove the damaged area, the deterministic processing method of milling has the advantage of precision and can process a fitted three-dimensional patch structure according to the stepped structure of the damaged area of ​​the material.

[0082] Table 4 Cutting depth results

[0083]

[0084] Embodiment 3

[0085] This embodiment provides a specific implementation method.

[0086] First, processing at the focal point achieves the performance of laser lift-off. Fig. 9 Optical microscope images of the ablated surface after laser processing are shown. Due to the multi-scale structural characteristics of plain woven CFRP (i.e., interwoven warp and weft yarns), there is an uneven surface with peaks and valleys in the orthogonal directions. A large amount of epoxy resin is filled between the warp and weft yarns. Therefore, it is challenging to achieve complete resin removal while maintaining fiber integrity due to the inherent structure. The results show that excessive surface energy density can lead to matrix degradation, fracture, and gasification.

[0087] Laser ablation parameters determine the surface ablation state. Compared with scanning speed, filling spacing and scanning mode, defocus is considered to be a more important factor, which directly affects the size of the laser spot diameter. Smaller spot diameter leads to higher surface energy density (E d=P / vd, where P is the laser power, v is the scanning speed, and d is the spot diameter), which is very sensitive to process parameters and difficult to control. Based on this, a series of positive bias laser ablation experiments were conducted, such as Fig.10 shown.

[0088] Based on the above research, in order to meet the needs of complex three-dimensional geometric repair, depth-controlled ablation combined with subsequent laser processing was used to achieve high-performance manufacturing of stepped repair geometries for plain-woven CFRP samples. The schematic diagram of the target sample has been Fig.11 The specific method is shown in Fig.12 As shown in the figure, the diameters of these geometric shapes are 2, 4 and 6 mm from top to bottom, respectively. The shaded area is the processing area. Its outer contour size is 8 mm × 8 mm. The plain woven CFRP samples were gradually ablated under the above-mentioned depth control conditions (v = 805 mm / s, d = 14 μm, N = 16, 32, 48). After laser stripping, the surface residue was treated by positive bias ablation method. Fig.13 As shown in the figure, these detailed features are presented through scanning electron microscope images. a1-a5 have not been processed by UV laser defocusing; b1-b5 have been processed by UV laser defocusing with parameters of v=625mm / s, d=20μm, N=1; c1-c5 have been processed by UV laser defocusing with parameters of v=750mm / s, d=30μm, N=1.

[0089] Under magnification, it is clearly observed that the fiber surface treated with special laser is cleaner, with no obvious resin residue on the surface. At the same time, the fiber integrity is guaranteed, without fiber breakage, fiber degradation and other damage. It proves that UV defocus processing can meet the cleaning needs within the range of 200μm-500μm removal depth, providing a reference for the high-quality surface forming of plain woven CFRP three-dimensional structures.

[0090] In order to analyze the milling removal mechanism of the material and characterize the microstructure, scanning electron microscope images were taken under different processing conditions. Due to the characteristics of the plain weave structure, the position of the yarn must be considered when studying the material removal process, because the fiber distribution at different positions will affect the material removal mechanism.

[0091] Fig.14 The surface morphology of different feeds per tooth in the upper meridian direction is shown. The specific milling positions are as follows: Fig.14(a). In this direction, the workpiece is squeezed, and the resin matrix is ​​smeared due to the angle between the fiber orientation and the feed direction. This phenomenon is particularly obvious at lower feed rates, as shown in Figure b1, where the surface is smooth and flat. Reducing the feed rate can reduce the generation of fiber fragments and improve the integrity of the carbon fiber. Conversely, increasing the feed per tooth will inhibit resin smearing. At the same time, fiber fragments and resin debris also increase. This is because the cutting edge contacts more material during the milling process, thereby generating greater milling forces. Plain woven CFRP is an anisotropic composite material. The greater the force, the greater the tool vibration, and the more fiber fragments and resin debris are generated, as shown in Figure d2. In order to confirm the presence of a large amount of resin residue on the surface, the specific milling parameters (v c =157m / min,f z =3μm / tooth, a p =350μm), as shown in Figures e and f. In addition to the C peak, the O peak proves the presence of a resin coating on the surface. In addition, it can be seen from the element distribution diagram that the distribution of the O element is almost complementary to that of the C element. This is because the resin matrix acts as an adhesive to bond the carbon fibers, resulting in the distribution of the O and C elements not coinciding. It is worth noting that the Au peak was generated by gold sputtering before obtaining the SEM image.

[0092] UV laser post-treatment is considered to be a method that can improve the surface quality of plain woven CFRP after milling. The corresponding microscopic surface features such as Fig.15As shown in the figure. Compared with the morphology after milling, UV laser ablation completely removes residual resin, fiber fragments and resin debris, while minimizing damage to the carbon fiber. The plowing marks on the fiber surface can be seen under magnification, which proves that the fiber is fresh and undamaged. Due to the huge difference in thermomechanical properties between epoxy resin and carbon fiber, epoxy resin is easier to remove than carbon fiber, so the unit energy density obtained after UV laser defocusing is easier to capture the resin removal threshold without damaging the fiber. These carbon fibers remain intact at the microscopic level, which is conducive to subsequent bonding repair. Although there are a small number of microcracks at the end of the carbon fiber, these microcracks are mainly caused by milling, and this mechanical damage cannot be repaired by UV laser ablation. Although the larger feed per tooth condition in the previous step will obtain poor surface quality, there will be no cracks at the end of the fiber after laser treatment, and excellent fiber integrity is obtained. In contrast, the smaller milling force generated by the smaller feed per tooth cannot completely break the fiber, so the cracks at the end of the fiber are exposed after laser ablation. In general, this two-step processing method may be more suitable for milling conditions with large feed per tooth, because it can maximize the integrity of the fiber, thereby improving the repair performance of subsequent bonding. Similarly, the EDS results after laser treatment were obtained under the same processing parameters. Obviously, there are almost no other elements on the surface except C element, which indicates that the laser post-treatment has removed the surface resin and obtained a large amount of intact carbon fiber.

[0093] Embodiment 4

[0094] This embodiment provides a specific implementation method.

[0095] 1. First, the ultraviolet laser single-channel scanning experiment was carried out by adjusting the laser scanning speed, filling spacing and defocusing amount, and the microscopic morphology was characterized. According to the surface ablation morphology, it was divided into three categories: severe ablation, partial ablation and incomplete ablation.

[0096] 2. A hybrid laser processing method is proposed to balance the efficient laser ablation under focal length conditions and the excellent surface quality obtained under off-focus conditions.

[0097] 3. Perform multiple scans under focal length conditions to obtain the relationship between cycle number and ablation depth.

[0098] In order to meet the needs of three-dimensional geometric repair, based on the relationship between the number of cycles and ablation depth under focal length conditions, depth-controlled ablation combined with subsequent laser defocus processing was used to achieve high-performance manufacturing of the stepped repair geometry of plain woven CFRP samples. When the removal depth was in the range of 200μm-500μm, the reliability of UV laser defocus processing in cleaning surface resin was verified.

[0099] 4. In order to meet the surface precision forming requirements of the patch in the damaged area of ​​the plain woven CFRP workpiece, the deterministic processing method of milling is used to remove the CFRP workpiece material.

[0100] 5. Milling experimental parameters As shown in Table 3, a total of 7 groups of experiments were designed based on single factor variables, which are milling depth, feed per tooth and cutting speed. The milling depth is determined according to the results of the UV laser repair experiment, and the depth range is 200μm-500μm.

[0101] 6. Characterize the microstructure of plain woven CFRP after milling and analyze the material removal mechanism. Reducing the feed rate per tooth under dry milling conditions can improve fiber integrity. In addition, under most conditions, a large amount of resin smearing and varying degrees of fiber fragments, resin debris, fiber peeling and cracks are inevitable.

[0102] 7. The milled material was processed using an ultraviolet laser defocusing method and the microscopic morphology was characterized. The laser removed a large amount of resin, fiber fragments and resin debris on the surface without destroying the fiber integrity.

[0103] 8. Use the same milling cutter to continuously process two three-dimensional stepped structures, and post-process the second solid geometry using UV laser defocus processing.

[0104] 9. Use a 3D profiler to obtain the surface profile before and after laser treatment, calculate the removal depth of milling and analyze the effect of laser repair on surface forming accuracy, such as Figure 7 and Figure 8 Obviously, laser treatment does not affect the removal depth accuracy of milling, because the laser only removes the surface resin debris and fiber fragments without damaging the carbon fiber body.

[0105] 10. Characterize the three-dimensional stepped geometry after laser processing, such as Fig.16 As shown. According to the characteristics of the stepped three-dimensional structure, the images obtained are all at right angles to each layer. Figure 6The images are arranged in the order from the upper left corner to the lower right corner in the figure, so there are a total of 6 locations displayed. Obviously, a large amount of surface smeared resin, fiber fragments, resin debris and separated carbon fiber tubes were cleaned up after laser treatment, although a small amount of debris still remained at the end of the fiber. Compared with the laser treatment performance after single-pass milling, the laser repair after three-dimensional forming still has some residues. This is because the surface area to be processed of the three-dimensional structure is increased. Compared with the narrow area of ​​single-pass milling, the residual resin on the surface may not be completely removed due to insufficient heat accumulation during the UV laser scanning process, so there will be some debris on the surface. In addition, since the result of UV laser treatment is based on the second three-dimensional structure processed by the same milling cutter, the surface of the milling cutter will have the material accumulated in the previous processing adhered to it, resulting in more serious resin smearing on the surface after milling.

[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0107] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-quality processing method for repairing a damaged area of ​​a plain woven CFRP, characterized in that: The following steps are involved: Step S1, firstly scanning a plain woven CFRP workpiece multiple times under a focal length condition to obtain a stepped workpiece with a close layer removed; Step S2, scanning the surface of the ablated CFRP workpiece under a defocus condition to clean the surface resin of the CFRP workpiece; Step S3, for the pit obtained after laser ablation, the workpiece is milled to obtain a patch matching the pit, and the surface resin and fiber fragments of the patch after milling are cleaned with ultraviolet laser; Step S4, bonding the processed patch to the CFRP workpiece to complete the repair of the CFRP workpiece.

2. A high-quality processing method for repairing a plain woven CFRP damaged area according to claim 1, characterized in that: In step S1, the scanning speed of scanning the plain weave CFRP workpiece is 115 mm / s-1840 mm / s, and the filling spacing range is 5 μm-28 μm.

3. A high-quality processing method for repairing a plain woven CFRP damaged area according to claim 1, characterized in that: In step S2, the speed range of scanning the surface of the CFRP workpiece under the defocus condition is 125 mm / s-750 mm / s, and the filling spacing range is 5 μm-30 μm.

4. The high-quality processing method for plain woven CFRP repair according to claim 3, characterized in that: In step S2, the scanning speed parameter is adjusted according to the following formula: Where v is the scanning speed, f is the frequency, and d is the spot diameter.

5. A high-quality processing method for repairing a plain woven CFRP damaged area according to claim 4, characterized in that: In step S2, the filling spacing parameter is adjusted according to the following formula: Where p is the fill spacing and d is the spot diameter.

Citation Information

Patent Citations

  • Surface pretreatment-repair method for composite material

    CN115609972A

  • Resin-based composite material laser connection and patching maintenance method

    CN115781028A

  • Carbon fiber composite material laser drilling and boring hole making method

    CN116372396A

  • Method and device for reducing CFRP (Carbon Fiber Reinforced Plastics) heat affected zone in laser processing

    CN118081069A

  • Method for burr-free machining of workpieces

    DE102009047995B3